Strategic Directions For The Design, Development, and Expansion of Transport Infrastructure in Ukraine - Karas, O.S. (Science and Innovation, 2024)
Introduction. Infrastructure is one of the key competitive advantages of Ukrainian regions. Certainly, Ukraine can and must generate high revenues from transportation services. This is preconditioned by its advantageous geopolitical location. However, the problem of poor quality in Ukraine has put its mark on each and every element of infrastructure. The situation gets further complicated by insufficient interaction between different industries within the transportation sector, scant investment inflows, outdated system of regulations, and rapid physical deterioration. Problem Statement. Infrastructure development is high on the agenda today, especially in view of the challenges and unsettled problems in this sector. The analysis of Ukraine’s competitiveness shows that transport infrastructure is the most dysfunctional component of the national infrastructure. Purpose. To develop preconditions for socio-economic growth of the country, to enhance the competitiveness of the national economy by improving the quality of transport services, developing the transport infrastructure and satisfying the social and commercial needs of the society, as well as to elaborate strategic directions for the public-private support of transportation as key industry of the economy. Materials and Methods. The theoretical and methodological basis of the research is the domestic and international legislative framework, scholarly research works of domestic and international researchers. To achieve the purpose of this research, the following methods have been used: general scientific and special research methods: analysis and synthesis, for studying the current state and experience of the transport infrastructure in Ukraine and the abstract-logical method, for making conclusions. Results. The author has elaborated a set of strategic directions for the development of transport infrastructure, as well as road, railway, air and waterborne transport, and identified the problems that impede effective development of the transport industry in Ukraine. The author has outlined directions for using the public-private partnership mechanisms based on concession agreements as a tool for realizing investment interests of the state and substantiated the feasibility of using the concession mechanism in the transport industry of Ukraine. Conclusions. The development of transport infrastructure remains among the priorities of the national economic reforms. The transport infrastructure unites all the regions and enterprises of Ukraine into a single state and integrates the Ukrainian economy into the world economy. It is necessary to create adequate conditions for attraction of private sector investments into the development of transport infrastructure and to focus efforts on using proper regulatory instruments for facilitating the financial involvement of the private sector.